Complete chloroplast genome of Rhus chinensis by de novo sequencing. Issue 1 (2nd January 2019) - Zuo, Ruihua; Sun, Chuanbo; Chen, Cunwu; Jiang, Ping
Abstract: Rhus chinensis is an important economic species, which could provide raw materials for pharmaceutical and industrial dyes. This is the first report of R. chinensis chloroplast genomes by de novo sequencing. The results showed that the length of R. chinensis was 159, 082 bp. The length of LSC and SSC was 85, 394 bp and 18, 663 bp, respectively. The genomes contained 126 genes, including 88 protein encoding genes, eight rRNA, and 30 tRNA genes. The clustering results showed that Anacardiaceae were closest to R. chinensis, followed by Aceraceae and Anacardiaceae.